Evaluation of Certain Definite Integrals Involving Generalized Hypergeometric Functions - Prathima Jayarama; Dongkyu Lim; Arjun K. Rathie; Adem Kilicman (Axioms, 2024)
In 2012, Chu investigated the generalization of classical Watson–Whipple–Dixon summation theorems in the form of analytical formulas. By employing four generalized Watson summation formulas, the objective of this paper is to evaluate a new class of several Eulerian-type integrals (single and double) and Laplace-type integrals involving a hypergeometric function. Several interesting special cases are also given. Symmetry arises spontaneously in the hypergeometric function.